Agricultural product prices - Tomek, William G., 1932-; Kaiser, Harry Mason (Ithaca : Cornell University Press, 2014)
'Published continuously since 1972, Agricultural Product Prices has become the standard textbook and reference work for students in agricultural and applied economics, buyers and sellers of commodities, and policymakers, clearly explaining conceptual and empirical models applicable to agricultural product markets. The new fifth edition uses up-to-date information and models to explain the behavior of agricultural product prices. Topics include price differences over market levels (marketing margins), price differences over space (regionally and internationally) and by quality attributes, and price variability with the passage of time (seasonal and cyclical variations, trends, and random behavior). William G. Tomek and Harry M. Kaiser review and adapt microeconomic principles to the characteristics of agricultural commodity markets and then apply these principles to the various dimensions of price behavior. They also provide an in-depth discussion of prices established for futures contracts and their relationship to cash (spot) market prices; cover the influential roles of price discovery institutions, such as auctions and negotiated contracts, and government policies regulating trade and farms; and discuss the specification, use, and evaluation of empirical models of agricultural prices, placing emphasis on the challenges of doing high-quality, useful analyses and interpreting results'--
Includes bibliographical references and indexes.
Keywords: Agricultural prices -- United States; Farm produce -- Prices -- United States